COVID-19: sudden and dramatic upsurge in the number of cases in India - Barot, Ketul S.; Naik, Saloni H.; Patel, Mehrie H.; Mankad, Saptak P.; Patel, Akash A.; Pandya, Pankti S.; Patel, Vishwa V.; Nimbalkar, Somashekhar M. (International Journal Of Community Medicine And Public Health, 2021)
The second wave of coronavirus disease 2019 (COVID-19) in India, which commenced in March’21, continues to create a major crisis of medications, hospital beds, oxygen, and Intensive Care Units at very rapid rate which has placed the country on the verge of a humanitarian crisis. While no definite treatment for SARS-CoV-2 has been found, different types of vaccines have been manufactured which have shown some effectiveness in preventing disease progression and severity. The objective of this manuscript is to review the available data from the pandemic and highlight the factors that have contributed to the development of second wave in India which has led to crisis. In this review, using available scientific literature on various indexes such as PubMed, Google Scholar, Medline and news articles- where appropriate, we dive into understanding newer virus variants, vaccines and their effectiveness against new strains, overwhelming burden on the Indian healthcare system and socio-politico-environmental factors responsible for upsurge. The sudden upsurge in the number of cases is multifactorial, which includes virus variants, complacency in following COVID-19 appropriate behaviour, burden over the health care system, various socio-politico-environmental factors. As the definitive treatment is yet to be discovered, vaccination remains at the top.